The Al-Qur'an Memorization Program as an Instrument for Religious Character Education for Islamic Boarding School Students - Mihmidaty Ya'cub; Moch. Sya’roni Hasan; Risa Aspiana; Humairourrohmah binti Mastor (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the formation of students’ religious character through the tahfidz Al-Qur’an program at Al-Azhar Islamic Boarding School, Mojowarno, Jombang. The research employed a qualitative approach with a case study design to gain an in-depth understanding of religious character education within the pesantren context. Data were collected through in-depth interviews, participatory observation, and documentation, involving the pesantren leader, tahfidz instructors, and students as research participants. Data validity was ensured through source and technique triangulation, while data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that students’ religious character is developed through the integration of religious habituation, exemplary behavior, and consistent discipline in daily pesantren life. The tahfidz Al-Qur’an program plays a significant role in shaping students’ religious character, including discipline, honesty, patience, consistency (istiqamah), and responsibility. Activities such as memorization submission, repetition (muroja’ah), and recitation evaluation (tasmi’) function not only as memorization assessments but also as effective means of internalizing religious values into students’ behavior. This study confirms that the tahfidz Al-Qur’an program serves not merely as a memorization activity but as an effective instrument for religious character education in Islamic boarding schools